Examining The Role of Social Media in Cultivating Brand Love Among Indonesia Youth: Insights for Local Cosmetics Brands - Chusnaini, Azmil; Rasyid, Reizano Amri; Muttaqiin, Ninnasi; Wulansari, Yuli Yanti (Universitas 17 Agustus 1945 Surabaya, 2024)
This research examines the role of social media marketing, perceived quality, and perceived price in cultivating brand love among Indonesian youth, particularly focusing on local fashion brands. Utilizing a sample size that provides robust statistical significance, the study confirms that social media marketing significantly influences both brand attitude (coefficient of 0.425) and brand trust (coefficient of 0.183). Perceived quality demonstrates a strong impact on brand attitude (coefficient of 0.783) and brand trust (coefficient of 0.724), underscoring the importance of high product standards. Additionally, perceived price is found to be a critical factor, with significant effects on brand attitude (coefficient of 0.894) and brand trust (coefficient of 0.347). The study also highlights the powerful relationship between brand attitude and brand love (coefficient of 0.883), as well as the influence of brand trust on brand love (coefficient of 0.348). These findings suggest that local fashion brands should strategically enhance their social media presence, maintain high product quality, and adopt fair pricing strategies to build strong emotional connections with consumers, thereby fostering brand love and loyalty. Future research should explore cross-industry comparisons, longitudinal impacts, and the role of emerging technologies in further enhancing these relationships